Efektffltas Pembelajaran Berasaskan Masalab (Problem Based Learning) Terhadap hasih Belajar Matematika Murid Sekolah Menengah Pertama di Pekanbaru (Jurnal Pilar Sains, 2006)
This is an experimental research using Problem Based Learning as a treatment. The objectiveresearch is identiI the effectiveness of the Problem Based Learning on mathematics achievement.Sample of 196 lower secondary student in Pekanbaru were used in the studies. The two treatmentgroup are from Madrasyah Tsanawiyah with 60 student in each group. The controlled consist of 76students from Junior High School. The first treatment Group using Problem Based Learning with‘media ceker’ While the second treatment Group using treatment Problem Based Learning with ‘lognumber line’. The control group is using a conventional teaching and learning method. There aremathematics achievement test. The research shows that the Problem Based Learning treatment moreeffectiveness on mathematics achievement than conventional learning. The Problem Based Learningimplicate that student active involvement in learning to solve problem will improve theirmathematics achievement effectively.